Electromyographic Characteristics of a Single Motion Shoulder Exercise: A Pilot Study Investigating a Novel Shoulder Exercise - Michael J Henehan; Tamar Brand-Perez; Jeffrey C Peng; Masaaki Tsuruike (North American Sports Medicine Institute, 2022)
# Background Shoulder exercises focused on strengthening the rotator cuff and scapular stabilizing muscles as well as addressing scapular dyskinesis and motor control have been shown to improve rotator cuff function and decrease shoulder pain. A single motion shoulder exercise that effectively activates the rotator cuff and scapular stabilizing muscles, engages the scapulohumeral rhythm, and includes eccentric contractions may be more effective and easier for patients to consistently perform as compared to multiple standard shoulder exercises. # Purpose To compare the electromyographic muscle activation of key shoulder complex muscles during a single motion exercise and individual exercises (standard exercises) typically included in shoulder rehabilitation protocols. # Study Design Case-controlled, cohort study # Methods Nineteen healthy men and women without shoulder pain or dysfunction were studied. Muscle activity of the rotator cuff and scapular stabilizing muscles (supraspinatus, infraspinatus, teres minor, trapezius \[upper, middle and lower\], serratus anterior, middle deltoid) was measured using surface EMG while subjects performed, in a standing position, several standard shoulder exercises typically included in shoulder rehabilitation protocols (resisted shoulder flexion, abduction in the scapular plane/scaption, external rotation, extension) and a single motion shoulder exercise consisting of a continuous movement creating the shape of "Figure of 8" in the transverse plane. The subjects used a weight between 5-15 pounds that produced muscle activation at 40-60% maximum voluntary isometric contraction (MVIC) for shoulder external rotation. That weight was then used for all of the exercises performed by the subject. The single highest EMG reading for each of the eight muscles studied, expressed as a percentage of MVIC, at any point during the second, third and fourth repetitions in a five repetition set was used to compare the single motion shoulder exercise and each exercise in the standard exercises set. # Results Ten men and nine women between 18-65 years of age were tested. No significant difference (p=.05) between the exercises was noted for the supraspinatus, infraspinatus, teres minor, serratus anterior, middle deltoid or upper trapezius. There was a significant difference favoring the standard exercises in the middle and lower trapezius. (p= 0.0109 and 0.0002 respectively) # Conclusion In this pilot study, muscle activation during the single motion, Figure of 8 pattern exercise was not significantly different from the standard shoulder exercises in six of eight key muscles that are usually included in shoulder rehabilitation protocols. The exceptions were the middle and lower trapezius which were activated to a significantly higher degree with the standard exercises. Further evaluation of the clinical effectiveness of the single motion shoulder exercise is needed. # Level of Evidence Level 3b